DOES MODIFIED COLLABORATIVE STRATEGIC READING (MCSR) AFFECT STUDENTS READING COMPREENSION?: AN EXPERIMENTAL STUDY OF ITERPERSONAL INTELLIGENCE - Qurrotul A'yun (Language-Edu, 2020)
Abstact:The objectives of the study were (1) to know whether modified collaborative strategic reading (MCSR) affect reading comprehension ability of the second grade students or not (2) to know which one the students who have high and low interpersonal intelligence on their reading comprehension (3) to know whether or not there is interaction between modified collaborative strategic reading and interpersonal intelligence.This study used factorial design. The population of this study was all of the classes at second grade at the school, and the researcher chose the sample using shuffle. Pre-test and post-test and also questionnaire were being the instrument of this study. The test consisted 30 items which had been validated by the expert, and it used content validity. It was proved by the result of analysis hypothesis testing that the sig. value on sig. (2-tailed) is 0.04. Actually, the sig. value (0.04) is lower than 0.05, so H0 is rejected. It means that MCSR had significant effect on students’ reading comprehension. Then, to get the result of the second and third research problem, this study used two-way ANNOVA. The answer is that there is interaction between MCSR and interpersonal intelligence on reading comprehension. Keywords: modified collaborative strategic reading,reading comprehension, interpersonal intelligence.